Influence of water absorption on the mechanical behavior of CFRPs manufactured by RTM at room temperature - Kirn Euniung; Jung, Do yun; Yu, Woong-Ryeol; Na, Won jin (IoP Institute of Physics, 2022)
Deterioration of the physical properties of fiber-reinforced composites is inevitable under a high temperature and humidity environment. The resin transfer molding (RTM) process for large composite parts is often accompanied by micropore formation, making the composite more sensitive to water absorption. In this study, carbon fiber-reinforced composite specimens were manufactured using the RTM process at room temperature, and their water absorption and mechanical properties were investigated. The water absorption was saturated after about 40 d, and the absorption ratio was higher at 75 ？C than at 50 ？C. The tensile strength of water-soaked specimens was decreased by 15%, exhibiting interlaminar delamination. However, plasticization of the cured epoxy resin by water increased interlaminar fracture toughness. These results indicate that water absorption accelerated interlaminar cracking initiated by micropore and interfacial failure in toughened resin, especially under low-temperature curing condition.